ASSESSING SNACK FOOD MANUFACTURERS’ CONFORMITY TO THE LAW ON FOOD LABELLING - Yuhanza Othman; Zuhairah Hasan; Mimi Sofiah Mustafa; Ida Rahayu Mahat; Marziana Abd Malib (International Journal of Accounting, Finance and Business, 2021)
Food labelling is one of the methods used by food manufacturers to communicate toconsumers concerning their product. Nevertheless, food manufacturers cannot simply labeltheir products based on their convenience. This is because the Food Act 1983 provides thatthose who fail to comply with any prescribed food standard commit an offence. The Ministry ofHealth through delegated power given by Section 34 of the Food Act 1983 has introduced theFood Regulation 1985 to prescribe the labelling particulars. Despite these two laws, there arecases where food manufacturers fail to follow food labelling regulations. Besides, the wordingand the label used are confusing the consumers. Thus, this research was conducted to assessthe food manufacturers’ conformity with the law of food labelling. The subject matter of thisstudy is a snack food that is categorised into sweet, chocolate, chips, crackers, biscuit and nuts.A convenience sampling method was used where the snack foods were purchased fromgroceries shop in Melaka and all data collected were analysed in SPSS. This study on foodlabelling is significant toward the consumers’ safety and at the same time would benefit thefood manufacturers in marketing their products.